ANALISA PENGARUH INTENSIF PAJAK TERHADAP KINERJA DAN NILAI PERUSAHAAN SETELAH ADANYA COVID-19 - Elvida Napitu, Feronika; Ngadiman, Ngadiman (ITB AAS Indonesia Surakarta, 2024)
This research was conducted to determine the effect of tax intensity on company performance and company value, and the effect of company performance on company value after Covid-19. The type of research used is a descriptive method with data collection techniques using purposive sampling techniques. Next, the data analysis technique is carried out by testing descriptive statistics and using multiple linear regression analysis. The objects of this research are the tourism, hospitality and transportation sectors listed on the Indonesia Stock Exchange. The samples found were 11 companies and produced 44 data that were processed in this research. The results of this research indicate that there is a positive influence between tax intensity on company performance and value, and a positive influence between company performance and company value. Based on this, the results of this research are expected to provide an overview of the intensive use of taxes by business actors in increasing company performance and value.